The Effect of Using Animated Audiovisual Media on Mastery of New Vocabulary in Grade 1 Students - aqizaadifa diva; Nadia Nur Faiza; Dian Srilestari; Eka Deviandari; Husnul Khotimah (CV Edujavare Publishing, 2026)
Vocabulary acquisition is a fundamental foundation in early childhood development, especially for first-grade students who are just entering formal language learning. Optimizing vocabulary acquisition can be supported through the implementation of interactive learning tools such as audiovisual animations. This study aims to describe the impact of audiovisual animation on vocabulary acquisition in early-grade elementary school students. Using a library research approach, data was collected through a comprehensive search of various scientific literature, including journal manuscripts, textbooks, and relevant previous research reports. The analysis phase included information condensation/reduction, data presentation, and drawing qualitative-descriptive conclusions. The research findings indicate that the use of animated audiovisual media has a significant positive impact on students' vocabulary acquisition. The harmonious collaboration between moving images and sound effects has been shown to improve students' focus, motivation to learn, active participation, and retention through adaptive and contextual presentation of material. A synthesis of various studies consistently confirms the reliability of this media in helping children understand, record, and apply new vocabulary. Therefore, audiovisual animation has great potential to be used as an adaptive alternative instructional media in grade I of elementary school.